Versatile Capacities and Missed Opportunities. A Case Study on Religious Minority Communities’ Roles in Urban Resilience Amidst COVID-19 in Helsinki, Finland - Turk, Jana Barbara (Diaconia, 2024)
Community resilience refers to the ability of local communities to manage crises and to the capacities of a community that allow it to participate in recovery from adversity. It is characteristic of crises that the public authorities cannot be expected to be able to manage everything centrally but that more decentralised action by various actors is needed from the bottom up. Religious communities can play a central role in community resilience, as they are usually rooted in local communities, operate at the grassroots level, are trusted among their adherents, and promote solidarity and communality. Religious communities had significant roles in community resilience during the COVID-19 pandemic. They collaborated with city officials, developed new working methods, took part in different networks, and supported people in their efforts to help each other. We will in this paper present results from an exploratory research project on religious communities’ roles in community resilience amidst the pandemic in Helsinki, the capital of Finland. We focus on six religious communities: three mosques and three Pentecostal churches, all of them multi-ethnic. Our data consist of expert interviews with the representatives of these religious communities. We analyse our results using the theoretical framework of adaptive capacities that promote community resilience, a theory formulated by Norris et al. (2008), and discuss the roles of religious minority communities amidst the pandemic, in relation to their context (Nordic welfare state, traditional majority church, urban diversity) and the the opportunities and challenges related to their roles in community resilience and urban resilience.